DESAIN DAN UJI COBA PENUNTUN PRAKTIKUM BERBASIS LEARNING CYCLE FASE 5E PADA MATERI KESETIMBANGAN KIMIA - Siti Maesaroh; Yuni Fatisa (Journal of Chemistry Education and Integration, 2022)
AbstractThis research is constituted by the available practicum guides that have not been able to develop the ability of students to be active and independent during the learning process in the laboratory. This research aimed at knowing the validity and practicality levels of the Learning Cycle 5E-based practicum guide on Chemical Equilibriumlesson.  The research design used was a 4D model which was limited to 3 stages, namely Define, Design, and Develop.  This research was administered at State Senior High School 4 Pekanbaru.  The subjects of this research were practicum guide media design experts, learning material experts, chemistry subject teachers and teachers at State Senior High School 4 Pekanbaru.  The object was Learning Cycle 5E based practicum guide on Chemical Equilibriumlesson.  The data were obtained from a questionnaire based on paper.  Validity and practicality test questionnaires were the instruments for collecting data.  The data obtained were analyzed by using qualitative and quantitative descriptive analysis techniques.  Based on the practicum guide developed was tested valid with a percentage of 94% (very valid), and it was tested practical with a percentage of 89% (very practical) on the data, it could be concluded that Learning Cycle 5E based practicum guide on Chemical Equilibrium lesson was valid and practical, So that it could be a teacher teaching material at school. Keywords : Chemical Equilibrium, Learning Cycle 5E, Practicum Guide